Theoretical Perspectives on Goods Market Equilibrium and Market Structure in The Indonesian Economy - Alfiyatun Ilmiyah; Devangga Putra Adhitya Pratama; Syamsul Arifin; Novita Aprilia (CV Pena Jaya Pers, 2025)
Purpose: This study examines theoretical perspectives on goods market equilibrium and links them to the heterogeneous market structure of the Indonesian economy to develop an integrated analytical framework. Design/methodology/approach: Hybrid systematic–scoping literature review following PRISMA guidelines and synthesizes macroeconomic and industrial organization theories through thematic coding and narrative analysis. Findings: The Indonesian’s good market equilibrium is structurally mediated by sectoral market concentration, pricing power, and regulatory arrangements, which influence output adjustment and fiscal policy transmission. Research limitations/implications: The study relies on literature synthesis without primary empirical testing, indicating the need for future quantitative research integrating concentration measures into macroeconomic models. Practical implications: The results suggest that policymakers should incorporate market structure considerations into fiscal and competition policies to improve economic stability and policy effectiveness. Originality/value: This study offers an integrative framework that bridges macroeconomic equilibrium theory with industrial organization analysis in the Indonesian context. Paper type: Literature review.